Development of Industry-Based Worksheets in Light Vehicle Engineering Teaching Materials - Tamamudin, Mukhammad; Sutopo, Yeri; Supraptono, Eko; Anis, Samsudin (Universitas Negeri Semarang, 2025)
Developing Industry-Based Job Sheets to Improve Student Competence in Electronic Fuel Injection (EFI) Tune-Up for the Light Vehicle Engineering Program at SMK Miftahul Huda. The main issue addressed in this study is students' low competency exam scores on EFI system materials, which result from the use of conventional learning media that do not meet industry standards. This research used a development research model with the Research and Development (R&D) approach, carried out through several stages: needs analysis, design, expert validation, limited trials, and effectiveness testing. Data was collected via expert validation questionnaires, practical questionnaires completed by teachers and students, and an effectiveness test using a pre-test and post-test control group design. Validation results showed that the job sheet was categorized as “highly valid,” with an average score of 4.85 from both media and material experts. The practicality test indicated that teachers and students rated the job sheet as “highly practical,” with an average score of 91.7%. Additionally, the effectiveness test demonstrated a significant improvement in the experimental class compared to the control class. The experimental class achieved an N-Gain score of 76.23% (high category), while the control class reached only 43.22% (medium category)